Encapsulating IM7-Displaying Yeast Cells in Calcium Alginate Beads for One-Step Protein Purification and Multienzyme Biocatalysis - Yin, Wenhao; Wang, Xinping; Liao, Ying; Ma, Lixin; Qiao, Jie; Liu, Hui; Song, Xin; Liu, Yi (Frontiers in Bioengineering and Biotechnology, 2022)
There are several commercial chromatographic systems for protein purification, however, development of cost-effective 3H-grade (high activity, high purity, and high activity) purification approaches is highly demanded. Here, we establish a methodology for encapsulating the IM7-displaying yeast cells in calcium alginate beads. Taking advantage of this biomaterial-based affinity chromatography, rapid and cost-effective purification of proteins with over 90% purity in a single step is achieved. Moreover, our system enables coating multienzyme complex to produce reusable immobilized cells for efficient cascade biotransformation. Together, the present method has great application potentials not only in the laboratory but also in industry for production of protein products as well as biocatalysis.